Queen Alia International Airport : The Role of IFC in Facilitating Private Investment in a Large Airport Project - Shi, Lin (International Finance Corporation, Washington, DC, 2018)
In 2007 Jordan lacked the financial resources and experience to embark on a renovation and expansion of its international airport, a colossal public-private undertaking. Yet by 2013 it was able to successfully complete the complex endeavor in collaboration with a private sector concessionaire, and without a sovereign guarantee, setting an example for countries and public-private project practitioners confronting similar circumstances. International Finance Corporation (IFC) played multiple roles in facilitating private investment over a 10-year period.